In silico analysis suggests interaction between Ebola virus and the extracellular matrix - Veljkovic, Veljko; Glisic, Sanja; Muller, Claude P.; Scotch, Matthew; Branch, Donald R.; Perovic, Vladimir R.; Sencanski, Milan; Veljkovic, Nevena; Colombatti, Alfonso (Frontiers in Microbiology, 2015)
The worst Ebola virus (EV) outbreak in history has hit Liberia, Sierra Leone and Guinea hardest and the trendlines in this crisis are grave, and now represents global public health threat concern. Limited therapeutic and/or prophylactic options which are available for humans suffering from Ebola virus disease (EVD) further complicate situation. Previous studies suggested that the EV glycoprotein (GP) is the main determinant causing structural damage of endothelial cells that triggers the hemorrhagic diathesis, but molecular mechanisms underlying this phenomenon remains elusive. Using the informational spectrum method (ISM), a virtual spectroscopy method for analysis of the protein-protein interactions, the interaction of GP with endothelial extracellular matrix (ECM) was investigated. Presented results of this in silico study suggest that Elastin Microfibril Interface Located Proteins (EMILINs) are involved in interaction between GP and ECM. This finding could contribute to better understanding of EV/endothelium interaction and its role in pathogenesis, prevention and therapy of EVD.